CROSSCUTTING RELIGIOUS EDUCATION FOR A BETTER SELF-UNDERSTANDING AS A RESPONSE TO RELIGIOUS EXTREMISM - Setyawan Andreas (IJIET (International Journal of Indonesian Education and Teaching), 2017)
Interreligious education has been recognized as alternative for mono-religious and multi-religious education in the Western World since 1990’s. This model underscores plurality both as a part of departure and as a possible result of religious education and at the same time it avoids a purely objective approach to the multitude of religions. However, there has been hardly any trace of interreligious education in Indonesia and in fact, even some people agree to abolish mono-religious education in the schools, which is considered to be vulnerable to favouritism and communal tensions. This study proposes a certain way of learning called cross-cutting religious education which may be applied within mono-religious model. The main concern is the following research questions: To what extent can crosscutting religious education lead to moderation and how can it provide cognitive, affective, and attitudinal dimensions which are required to restrain the tendency of religious extremism? The author argues that a crosscutting religious education in high schools through religious literature provides a better self-understanding which in the long term reduces the tendency of religious extremism. Thus, the study shows a method of hermeneutics which results in a better self-understanding of certain religious tradition based on the reading of different religious tradition texts.